Immediate Pre-Partum SARS-CoV-2 Status and Immune Profiling of Breastmilk: A Case-Control Study - Sánchez García, Laura; Gómez-Torres, Natalia; Cabañas, Fernando; González-Sánchez, Raquel; López-Azorín, Manuela; Moral-Pumarega, M. Teresa; Escuder-Vieco, Diana; Cabañes-Alonso, Esther; Castro, Irma; Alba, Claudio; Rodríguez Gómez, Juan Miguel; Pellicer, Adelina (Frontiers in Immunology, 2021)
OBJETIVE: To address the prevalence of SARS-CoV-2 and the evolutionary profile of immune compounds in breastmilk of positive mothers according to time and disease state. METHODS: Forty-five term pregnant women with confirmed non-severe SARS-CoV-2 infection (case group), and 96 SARS-CoV-2 negative women in identical conditions (control group) were approached, using consecutive sample. Weekly (1st to 5th week postpartum) reverse transcription polymerase chain reaction (RT-PCR) in nasopharyngeal swabs (cases) and breastmilk (cases and controls) were obtained. Concentration of cytokines, chemokines and growth factors in breastmilk (cases and controls) were determined at 1st and 5th week post-partum. RESULTS: Thirty-seven (study group) and 45 (control group) women were enrolled. Symptomatic infection occurred in 56.8% of women in the study group (48% fever, 48% anosmia, 43% cough). SARS-CoV-2 RNA was not found in breastmilk samples. Concentrations of cytokines (IFN-γ, IL-1ra, IL-4, IL-6, IL-9, IL-13 and TNF-α), chemokines (Eotaxin, IP-10, MIP-1α and RANTES) and growth factors (FGF, GM-CSF, IL7 and PDGF-BB) were higher in breastmilk of the study compared to the control group at 1st week postpartum. Immune compounds concentrations decreased on time, particularly in the control group milk samples. Time of nasopharyngeal swab to become negative influenced the immune compound concentration pattern. Severity of disease (symptomatic or asymptomatic infection) did not affect the immunological profile in breast milk. CONCLUSIONSThis study confirms no viral RNA and a distinct immunological profile in breastmilk according to mother’s SARS-CoV-2 status. Additional studies should address whether these findings indicate efficient reaction against SARS-CoV-2 infection, which might be suitable to protect the recipient child.